Interpreting the landscape of human occupation in Fuego-Patagonia (-51° -55° S) during the lateglacial-Holocene - (:unkn) unknown (My University, 2025)
Southern South America (SSA) plays a key role for palaeoenvironmental and climatic reconstructions across a range of spatial scales. The key geographical location of Fuego-Patagonia (~51°-55°S) and its complex topography have created a unique and sensitive vegetation ecosystem. The changes in the distribution and abundance of the vegetation forest/steppe ecotone are closely linked to large-scale controls by regional and global climate. This project takes advantage of the high sensitivity of the forest/steppe ecotone ecosystem to reconstruct the nature and timing of environmental changes during the early peopling of Fuego-Patagonia. Previous palynological records in Fuego-Patagonia are largely focused on climate reconstructions and not the human dynamics across the changing landscape during the Lateglacial / interglacial transition (LGIT) and the Holocene. The principal goal of this study is to integrate the evidence for past environmental changes and the evidence for human occupation in Fuego-Patagonia during the Lateglacial to the Holocene. In order to assess the linkages between the landscape and human activity, it is instructive to examine the archaeological record and compare it to increasingly detailed palaeoenvironmental records from different ecosystems generated previously and by this study. Archaeological evidence from continental Patagonia and central-northern Tierra del Fuego suggests early human occupation during the LGIT (c.12,800–10,500 Cal yr BP). However, the later record of human occupation during the Holocene is temporally and geographically discontinuous. To date, archaeological evidence has not been integrated with the palaeoenvironmental information from the surrounding environments. This study will explore the hypotheses that i) the first human occupation was an initial process of human exploration across Fuego-Patagonia during the LGIT and the discontinuous development of human communities was in response to the substantial changes in vegetation patterns (i.e. the vital resources for humans) triggered by dramatic shifts in climate; ii) the continuous evidence for relatively intense and longer-term occupations at Pali-Aike (Cueva Fell) may be related to more stable climatic condition around the area, contrary to a general climatic pattern in western areas of the region. These hypothesis can be clarified comparing three paleoenvironmental record with its respective archaeological evidence (each study case) and then be integrated in the regional network of palynological record and, iii) the earliest evidence for the first maritime hunter-gatherers around Estrecho de Magallanes was likely linked to regional-wide landscape modification as a maximum of rise in sea level registered in the Estrecho de Magallanes (Puerto del Hambre) by c.7,400 Cal yr BP (McCulloch and Davies, 2001) and under high fluctuation of climatic conditions during the mid-Holocene. This study will produce two new high-temporal resolution palaeoenvironmental records closely linked to the key archaeological sites at Última Esperanza (~51°S) and Isla Navarino (~55°S). The past landscapes will be reconstructed using the powerful technique of pollen analysis (i.e. vegetation change) and supported by sediment geochemistry. The past environmental changes will then be integrated into a network of extant palaeoenvironmental data to reconstruct the past landscape changes and the evidence for first human occupation across the Fuego-Patagonian region during the LGIT and the Holocene. This regional record of landscape change will then be compared and contrasted with the archaeological records of human occupation from Fuego-Patagonia, including the latest evidence from Última Esperanza. This interdisciplinary Project represents a timely opportunity to bring together high-resolution continuous palaeoenvironmental records with evidence of the changing human and cultural landscape to advance our understanding of the process and drivers of human migration and colonisation.